1999
DOI: 10.1177/070674379904400207
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Haloperidol Dosage in First-Episode Psychosis

Abstract: Many people suffering a first psychotic episode respond to haloperidol doses well below levels in common use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…Increasing the dose to 3-4 mg/day led to 5 of the 9 participants in this group meeting response criteria, an overall response rate of 73%. Zhang-Wong and coworkers [14] reported a 42% response rate with 2 mg of haloperidol in FEP, while higher dose risperidone (mean dose 6.1 mg) and haloperidol (mean dose 5.6 mg) led to 63% and 56% response in FEP patients, respectively [16]. In our study, a similar response rate as that observed by Emsley and colleagues [16] was achieved with one-third to half the dose of risperidone.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increasing the dose to 3-4 mg/day led to 5 of the 9 participants in this group meeting response criteria, an overall response rate of 73%. Zhang-Wong and coworkers [14] reported a 42% response rate with 2 mg of haloperidol in FEP, while higher dose risperidone (mean dose 6.1 mg) and haloperidol (mean dose 5.6 mg) led to 63% and 56% response in FEP patients, respectively [16]. In our study, a similar response rate as that observed by Emsley and colleagues [16] was achieved with one-third to half the dose of risperidone.…”
Section: Discussionsupporting
confidence: 87%
“…Symptomatic improvements have been described using low-dose haloperidol at 3.4 mg/day [13, 14], low-dose olanzapine at 9.1 mg/day [15], and risperidone at doses of less than 6 mg daily [16, 17]. Superiority has also been demonstrated for the use of low-dose risperidone (mean 3.3 mg) over haloperidol (mean 2.9 mg) in terms of prevention of relapse and time to relapse in first-episode patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…First, the persistence of FGA prescription at higher doses than the recommended on international consensus [3-6] may be related to the belief on "rapid neuroleptization" or impregnation for the management of an aggressive and agitated psychotic patient; and second, the use of low doses of these drugs reflects the preference for prescribing threshold or minimum effective doses. Many studies on the effectiveness of this approach have been published [31-36]. This strategy is based on the finding that clinical response is reached with 65% dopamine D 2 receptor occupancy.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose therapies have mostly been judged inappropriate in the past clinical trials (Putten et al 1990;Zhang-wong et al 1999;Suzuki et al 2003), and the chlorpromazine equivalent doses of 300-600 mg/day are recommended in the maintenance phase (Lehman et al 2004).…”
Section: Introductionmentioning
confidence: 99%